A silicone resin, a method for preparing the same, and a heavy-duty anticorrosive coating

CN122978446APending Publication Date: 2026-10-27ZHEJIANG TIANTIE SCIENCE & TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611161352.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

现有的溶剂型涂料虽然防护性能优异,但存在污染大、对海洋生态环境和施工人员健康危害显著的问题;水性涂料虽环保性较好,但耐候性、耐盐雾和抗生物吸附等性能欠缺;无溶剂涂料虽能减少污染,增强涂料耐化学腐蚀性,但施工工艺复杂;而纳米复合涂料虽在表面屏蔽性和机械强度上有所突破,但存在成本高、推广受限的问题

Benefits of technology

本发明提供的有机硅树脂为一种绿色环保树脂,有害物质(如甲醛、甲苯、苯、重金属等)不超过相关标准要求检出限;常温下即可固化成膜,无需采取加温等手段促进固化;引入更低表面能的氟官能团,使其各项技术指标得到显著改善;适用性广,能满足各类环境条件下混凝土及钢结构构筑物防护要求;环境适应性强,可适应干湿、冻融、海洋、强腐蚀等环境;一次施工,后期维护成本低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The application discloses a kind of organic silicon resin and preparation method thereof, heavy-duty anticorrosive coating, it is related to heavy-duty anticorrosive coating technical field. Green and environmentally friendly organic silicon resin is prepared by compounding di-functional silane and tri-functional silane. Organic silicon resin can be cured into film at room temperature, without taking means such as heating to promote curing. It has excellent anti-fouling and anti-absorption performance. It has wide applicability and can meet the protection requirements of concrete and steel structure under various environmental conditions. It has strong environmental adaptability and can adapt to dry and wet, freeze-thaw, marine, strong corrosion and other environments. One construction, low maintenance cost in later period. The preparation process of organic silicon resin is simple, the process is simplified, and it can be sprayed, rolled and brushed conventionally without special equipment. Used in heavy-duty anticorrosive coating can effectively protect metal structure from corrosion, greatly improve the carbonation resistance and chloride ion penetration resistance of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heavy-duty anti-corrosion coatings, and more specifically, to an organosilicon resin, its preparation method, and a heavy-duty anti-corrosion coating. Background Technology

[0002] With the rapid development of the marine economy, offshore wind power, cross-sea bridges, coastal infrastructure, and water-related infrastructure, the corrosion problem of concrete and steel structures in marine climates has become increasingly prominent. With increasing environmental awareness and the advancement of sustainable development strategies, environmentally friendly heavy-duty anti-corrosion coatings have been widely applied. Among these, solvent-based, water-based, solvent-free, and nanocomposite technologies have emerged, significantly improving the environmental friendliness and protective performance of coatings, leading to their widespread application in industrial corrosion protection, marine engineering, and energy facilities.

[0003] In marine climates, heavy-duty anti-corrosion coatings face even more stringent challenges. High salt spray, high humidity, strong ultraviolet radiation, and microbial adhesion place higher demands on the long-term protective performance of these coatings. While existing solvent-based coatings offer excellent protection, they suffer from significant pollution and pose substantial risks to the marine ecosystem and the health of construction workers. Water-based coatings, though more environmentally friendly, lack resistance to weathering, salt spray, and biosorption. Solvent-free coatings reduce pollution and enhance chemical corrosion resistance, but their application processes are complex. While nanocomposite coatings have made breakthroughs in surface shielding and mechanical strength, their high cost limits their widespread adoption.

[0004] Therefore, current technologies still struggle to balance multiple demands such as environmental friendliness, cost, long-lasting effects, weather resistance, and antimicrobial properties. How to further promote the sustainable development of this field through material innovation and process optimization has become one of the urgent technical challenges to be solved in this field.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide an organosilicon resin and its preparation method, as well as a heavy-duty anti-corrosion coating, to solve or improve the above-mentioned technical problems.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides an organosilicon resin comprising a difunctional silane and a trifunctional silane in a molar ratio of (6-9):(2.5-8.5); The difunctional silane is selected from at least one of methylphenyldimethoxysilane, dimethyldimethoxysilane, and methylphenylfluoroalkylsilane; The trifunctional silane is selected from at least one of methyltrimethoxysilane, trifluoropropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.

[0008] Secondly, the present invention provides a method for preparing an organosilicon resin as described in any of the foregoing embodiments, comprising the following steps: After mixing all the raw materials of the organosilicon resin with the solvent in proportion, a hydrolysis reaction is carried out under an inert atmosphere and at a temperature of 50℃-60℃. After the hydrolysis reaction is completed, the temperature is raised to 60℃-80℃ to carry out a polycondensation reaction. After neutralization reaction, alcohol removal treatment and vacuum dehydration treatment, the organosilicon resin is obtained. The total time for hydrolysis and condensation reactions is ≤6h.

[0009] Thirdly, the present invention provides a heavy-duty anti-corrosion coating, comprising an organosilicon resin as described in any of the foregoing embodiments or an organosilicon resin prepared by any of the foregoing embodiments.

[0010] The present invention has the following beneficial effects: The organosilicon resin provided by this invention is a green and environmentally friendly resin, with harmful substances (such as formaldehyde, toluene, benzene, heavy metals, etc.) not exceeding the detection limits of relevant standards; it can be cured into a film at room temperature without the need for heating or other means to promote curing; the introduction of fluorine functional groups with lower surface energy significantly improves its various technical indicators; it has wide applicability and can meet the protection requirements of concrete and steel structures under various environmental conditions; it has strong environmental adaptability and can adapt to dry and wet, freeze-thaw, marine, and highly corrosive environments; it requires only one application and has low maintenance costs.

[0011] The preparation process of silicone resin is simple and the steps are simplified. It can be applied by conventional spraying, rolling, or brushing without the need for special equipment.

[0012] Heavy-duty anti-corrosion coatings made from organosilicon resins possess superior hydrophobicity and UV resistance. Their small-size effect and macroscopic quantum tunneling effect induce seepage, while also exhibiting thermal, light, and chemical stability. This enhances the product's anti-aging, chemical, erosion, and acid / alkali resistance, along with its high salt spray resistance, effectively protecting metal structures from corrosion. Furthermore, it significantly improves the carbonation resistance and chloride ion penetration resistance of concrete. Detailed Implementation

[0013] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0014] In a first aspect, the present invention provides an organosilicon resin comprising a difunctional silane and a trifunctional silane in a molar ratio of (6-9):(2.5-8.5); The difunctional silane is selected from at least one of methylphenyldimethoxysilane, dimethyldimethoxysilane, and methylphenylfluoroalkylsilane; Furthermore, difunctional silanes include methylphenyldimethoxysilane and dimethyldimethoxysilane. Trifunctional silanes include methyltrimethoxysilane, trifluoropropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.

[0015] The trifunctional silane is selected from at least one of methyltrimethoxysilane, trifluoropropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.

[0016] For example, a difunctional silane refers to a silane containing two active functional groups that can participate in a reaction. Difunctional silanes can also be referred to as D-type silanes, and trifunctional silanes can also be referred to as T-type silanes.

[0017] Methylphenyl dimethoxysilane (MPDMS), a difunctional (D-type) compound, introduces phenyl and methoxy groups into silicone resins, which are dominant in terms of heat resistance and adhesion strength.

[0018] Dimethyldimethoxysilane (DMDMS), a difunctional (D-type) compound, plays a dominant role in toughness / reducing brittleness and crosslinking density in silicone resins.

[0019] Methyltrimethoxysilane (MTMS), a trifunctional (T-type) compound, provides methyl and methoxy groups in silicone resins, dominating crosslinking and hardness.

[0020] Trifluoropropyltrimethoxysilane (TFPTMS), a trifunctional (T-type) compound, provides fluorine units in silicone resins, dominating hydrophobicity, oil resistance, and low surface energy.

[0021] γ-aminopropyltriethoxysilane (KH-550, trifunctional, T-type) introduces amino groups into silicone resins. The curing mode and adhesion strength can be controlled by adjusting the amount of amino groups. It can be self-cured by high-temperature heating or cross-linked and cured at room temperature.

[0022] By controlling the reaction temperature and pressure, catalyst, neutralizing agent, etc., methylphenylfluoroalkylsilanes with satisfactory performance can be prepared. The organosilicon resin provided by this invention is based on the lotus leaf biomimetic superhydrophobic interface construction theory. It employs a composite synthesis process combining the sol-gel method with hydrolysis condensation-multi-component random copolymerization to achieve covalent bonding and three-dimensional network structuring of functional monomers such as methylmethoxysilane, phenylmethoxysilane, and trifluoropropyltrimethoxysilane, resulting in a resin with hydrophobic, antifouling, and anti-adsorption properties. The specific synthesis principle is analyzed as follows: First, using deionized water and organic solvent as a composite dispersion system, under mild catalytic conditions, three types of silane monomers—methylmethoxysilane, phenylmethoxysilane, and trifluoropropyltrimethoxysilane—underwent simultaneous hydrolysis. The methoxy groups in each monomer molecule broke, generating active silanol intermediates rich in silanol hydroxyl groups (-Si-OH), forming a homogeneous and stable primary sol system. During this process, the phenylmethoxysilane monomer introduced rigid phenyl side groups, ensuring the structural stability and mechanical properties of the resin matrix, while the trifluoropropyltrimethoxysilane monomer introduced long-chain fluoroalkyl functional groups, laying the molecular foundation for the subsequent formation of low surface energy interfaces.

[0023] Subsequently, the active silanol intermediates in the primary sol undergo intermolecular and intramolecular dehydration and de-alcoholization condensation reactions under the synergistic effect of heating and catalysis. The silanol groups cross-link to form Si-O-Si inorganic silicon-oxygen bonds, gradually generating linear and branched prepolymers. With the continuous cross-linking of the prepolymers, the sol system gradually transforms into a gel system, completing the sol-gel phase transition. During this phase transition, the condensation reaction and copolymerization reaction are carried out simultaneously through reaction kinetic control. The three types of monomers randomly copolymerize through Si-O-Si covalent bonds to construct a three-dimensional network organic-inorganic hybrid silicone resin framework. At the same time, they self-assemble in situ to form a nanoscale micro-rough structure, accurately replicating the biomimetic topological structure of the micro-nano dual roughness of the lotus leaf surface, avoiding complex processes such as subsequent physical etching.

[0024] In the later stage of the condensation-copolymerization reaction, by controlling the reaction temperature and system pH, the fluoropropyl side chains are spontaneously enriched and arranged in an orderly manner at the air-resin interface during the resin film formation process, which greatly reduces the surface free energy of the material. The resulting nano-methylphenyl fluoroalkyl organosilicon resin has the synergistic effect of biomimetic micro-nano rough structure and low surface energy fluoroalkyl modification layer, which blocks liquid wetting and pollutant adhesion from the perspective of interface wetting principle, endowing the material with excellent hydrophobic, antifouling and interface anti-adsorption properties, and the three-dimensional network copolymer structure ensures the resin's weather resistance and structural stability.

[0025] In an optional embodiment, the difunctional silane comprises methylphenyldimethoxysilane and dimethyldimethoxysilane in a molar ratio of 4:(2-5).

[0026] Furthermore, in the difunctional silane, the molar ratio of methylphenyldimethoxysilane to dimethyldimethoxysilane can be selected from any one of 4:2, 4:3, 4:3.5, 4:4, 4:4.5 and 4:5, or other values ​​in the range of 4:(2-5).

[0027] When the molar ratio of dimethyldimethoxysilane changes, it affects the crosslinking density and toughness of the resin; the specific analysis is as follows: When the ratio is less than 4:2, the synthetic resin is rigid and has high hardness but poor flexibility, and gelation is likely to occur during synthesis. When the ratio is in the range of 4:(2-5), such as 4:3, the crosslinking density and flexibility of the resin are significantly improved, the synthesis control is better, the hardness is higher, and the adhesion is better. When the ratio is 4:4, the crosslinking density and flexibility are relatively balanced, the hardness and adhesion are better, the system viscosity is lower, the storage is stable, and it is suitable for use environments with certain requirements for impact resistance and bending. When the ratio is greater than 4:5, the system has a high proportion of linear segments, the crosslinking density decreases, the molecular weight is easily insufficient, the resin is more flexible, the hardness and adhesion decrease, the water resistance is relatively poor, and it is suitable for use environments with more elastic coatings in anhydrous environments.

[0028] In an optional embodiment, the trifunctional silane includes methyltrimethoxysilane, trifluoropropyltrimethoxysilane and γ-aminopropyltriethoxysilane in a molar ratio of 2.5:(1-3):(1-3).

[0029] Furthermore, in the trifunctional silane, the molar ratio of methyltrimethoxysilane, trifluoropropyltrimethoxysilane, and γ-aminopropyltriethoxysilane can be selected from any one of 2.5:1:1, 2.5:1.5:1, 2.5:2:1, 2.5:3:1, 2.5:1:2, 2.5:1:3, 2.5:2:3, 2.5:3:2, and 2.5:3:3, or other values ​​within the range of 2.5:(1-3):(1-3).

[0030] It should be noted that trifluoropropyltrimethoxysilane provides fluorine units in organosilicon resins, primarily exhibiting hydrophobicity, oil resistance, and low surface energy. When its dosage is too low, it provides a low-fluorine molecular chain with the following characteristics: few and sparsely distributed trifluoropropyl side chains, a main chain dominated by methylphenyl groups, moderate crosslinking density, good chain segment flexibility, moderate silanol group residue, sufficient exposure of amino sites, high activation, no phase separation, and excellent chain segment compatibility.

[0031] When the amount of trifluoropropyltrimethoxysilane is moderate, it provides a medium-fluorine molecular chain with the following molecular structure characteristics: moderate number and uniform distribution of trifluoropropyl side chains, forming a balance with methyl and phenyl groups, moderate to high crosslinking density, a balance between rigidity and flexibility of chain segments, dense and uniform network, residual silanol groups matching the requirements of amino curing, moderate activation, no macroscopic phase separation, microscopic controllable migration of fluorine segments to the surface to form a hydrophobic layer.

[0032] When the amount of trifluoropropyltrimethoxysilane is too high, it provides a high-fluorine molecular chain with the following characteristics: a large number of highly dense trifluoropropyl side chains, the main chain is wrapped by fluorine side chains, the cross-linking density is high, the chain segments are rigid and the branching degree is high; the silanol group is easily shielded by the fluorine side chain site, the activation decreases, and incomplete curing is likely to occur; the compatibility between the fluorine chain segment and the silicon chain segment decreases, and phase separation is likely to occur.

[0033] γ-aminopropyltriethoxysilane introduces amino groups into silicone resins. Controlling the amount of amino groups controls the curing mode and adhesion strength, allowing for self-curing at high temperatures or cross-linking curing at room temperature. When used in small amounts, the amount of amino groups introduced is small, which is beneficial for storage. It also exhibits cross-linking activity. Later introduction of amino curing agents helps improve the completeness of curing, resulting in high workability, easy control over the production process of protective materials, and a long storage time.

[0034] When the amount of γ-aminopropyltriethoxysilane is increased, the resin can achieve room temperature self-curing, the cross-linked network is dense, and the film-forming performance is optimal, but the storage performance is slightly worse, which is not conducive to subsequent steps and long-term storage.

[0035] When too much γ-aminopropyltriethoxysilane is used, the resin curing rate is significantly too fast and the application window is short. Excessive amino content leads to severe embrittlement, yellowing, and other phenomena, making subsequent processing impossible.

[0036] To meet the stringent requirements of stain-resistant, self-cleaning, and anti-adsorption heavy-duty anti-corrosion coatings, the compatibility of the formulation with various substrates must be considered, especially the thermal expansion and contraction characteristics of the structure caused by anisotropic structures and temperature differences, to ensure that the material has excellent processing rheological properties; at the same time, it should support flexible adjustment of the curing agent ratio on-site according to working conditions to achieve immediate mixing and construction; in the preferred embodiment of the present invention, the organosilicon resin includes methylphenyl dimethoxysilane, dimethyl dimethoxysilane, methyltrimethoxysilane, trifluoropropyltrimethoxysilane, and γ-aminopropyltriethoxysilane in a molar ratio of 4:4:2.5:2:1.

[0037] Secondly, the present invention provides a method for preparing an organosilicon resin as described in any of the foregoing embodiments, comprising the following steps: The raw materials of organosilicon resin are mixed with solvent in proportion, and then hydrolyzed under an inert atmosphere at a temperature of 50℃-60℃. After the hydrolysis reaction is completed, the temperature is raised to 60℃-80℃ to carry out a polycondensation reaction. After neutralization reaction, alcohol removal treatment and vacuum dehydration treatment, organosilicon resin is obtained. The total time for hydrolysis and condensation reactions is ≤6h.

[0038] Specifically, the preparation method of organosilicon resin includes the following steps: Four types of organosilicon resin raw materials (excluding γ-aminopropyltriethoxysilane) are mixed with a solvent in a specific ratio, and then subjected to a hydrolysis reaction under an inert atmosphere at a temperature of 50℃-60℃; after the hydrolysis reaction is completed, a mixture of γ-aminopropyltriethoxysilane and anhydrous ethanol is added dropwise, and the mixture is kept at a constant temperature and stirred for 25-35 minutes, then heated to 60℃-80℃ to carry out a polycondensation reaction; after neutralization, de-alcoholization, and vacuum dehydration, the organosilicon resin is obtained. The reaction vessel should be selected appropriately based on the required amount of raw materials. The inert atmosphere can be nitrogen, helium, or other gases as needed.

[0039] In this invention, the total time for hydrolysis and condensation reactions (abbreviated as hydrolysis-condensation time) is controlled at 6 hours. During this stage, the silicone resin is in a controllable growth stage, in which the silanol groups (Si-OH) are not completely reacted, retaining subsequent curing activity, and the number-average molecular weight Mn is moderate, maintained at 3000 g / mol-8000 g / mol.

[0040] The control of the number-average molecular weight of the organosilicon resin in the embodiments of the present invention is beneficial to ensuring the uniformity and stability of the paint film when the resin is coated. The linear slightly branched structure provides sufficient physical properties such as resin flexibility and impact resistance, while supporting sufficient cross-linking network to ensure sufficient curing and functional group incorporation, without causing performance imbalance due to excessive incorporation of functional groups. It should be noted that when the hydrolysis-condensation time is controlled between 6h and 24h, the molecular weight of the silicone resin steadily increases, the degree of branching of the molecular chain increases, and the viscosity of the system gradually increases. In the early stage, it still maintains a fluid state, but after 12h, the degree of branching increases significantly and the viscosity of the system increases significantly. When the hydrolysis-condensation time is ≥24h, the molecular chain undergoes deep cross-linking, and the system changes from a transparent viscous liquid to a translucent gel, eventually losing its fluidity and becoming unsuitable for use in heavy-duty anti-corrosion coatings.

[0041] The other four organosilicon resins, excluding γ-aminopropyltriethoxysilane, are reacted first, and then γ-aminopropyltriethoxysilane is added. This can prevent the alkaline aminosilane from being introduced too early and undergoing hydrolysis under acidic conditions, which would disrupt the system's reaction equilibrium and lead to excessive polycondensation or insufficient reaction of some silanes, thus affecting the resin synthesis results.

[0042] In an optional embodiment, the ratio of the total mass of the silicone resin raw materials to the mass of the solvent is 1:(0.9-1.2). The raw materials for the organosilicon resin include methylphenyl dimethoxysilane, dimethyl dimethoxysilane, methyltrimethoxysilane and trifluoropropyltrimethoxysilane in a molar ratio of 4:(2-5):2.5:(1-3); the solvent is selected from at least one of n-butanol, isopropanol and anhydrous ethanol.

[0043] It should be noted that the raw materials of the organosilicon resin include methylphenyldimethoxysilane, dimethyldimethoxysilane, methyltrimethoxysilane and trifluoropropyltrimethoxysilane; the total mass of the raw materials and the mass of the solvent can be selected from any one of 1:0.9, 1:1, 1:1.1 and 1:1.2, or other values ​​in the range of 1:(0.9-1.2).

[0044] Furthermore, the total mass ratio of the raw materials to the solvent of the silicone resin is 1:1.

[0045] In an optional embodiment, the solvent comprises n-butanol and anhydrous ethanol in a mass ratio of 1:(0.8-1.1). Exemplarily, the mass ratio of n-butanol to anhydrous ethanol may be selected from any one of 1:0.8, 1:0.9, 1:1, and 1:1.1, or other values ​​in the range of 1:(0.8-1.1).

[0046] Anhydrous ethanol is a highly polar solvent that is soluble in water, which is beneficial for controlling the hydrolysis rate and ensuring a homogeneous system; its low boiling point makes it easy to remove later.

[0047] n-Butanol is a moderately polar solvent that can dissolve functional segments such as phenyl and trifluoropropyl groups; it is beneficial for controlling condensation efficiency, inhibiting resin gelation, delaying condensation, and reducing crosslinking density; its boiling point is higher than that of anhydrous ethanol, which is beneficial for achieving gradient temperature control in post-processing.

[0048] The use of a combination of n-butanol and anhydrous ethanol as solvents helps to balance the polarity of the resin system and avoids deviations in synthesis efficiency due to heterogeneous solubility. The hydrolysis and condensation efficiencies during resin preparation are controllable, preventing burst polymerization or burst coagulation. The controlled evaporation temperature gradient facilitates solvent removal, resulting in low residue and good resin film quality.

[0049] Furthermore, the solvent includes n-butanol and anhydrous ethanol in a mass ratio of 1:1.

[0050] In an optional embodiment, the hydrolysis reaction has at least one of the following characteristics: Feature 1: The hydrolysis reaction takes place in a water bath environment for 1-2 hours; Feature 2: The hydrolysis reaction is subjected to stirring at a speed of 300 r / min-400 r / min; Feature 3: The pH of the hydrolysis reaction system is 2.0-4.0, and the pH adjuster is selected from at least one of hydrochloric acid, sulfuric acid, citric acid, phosphoric acid and acetic acid; the amount of pH adjuster used is 0.6%-0.8% of the total amount of organosilicon resin raw materials.

[0051] This invention conducts the hydrolysis reaction in a water bath environment to avoid excessively high temperatures that could cause the silanol groups (Si) to degrade. Excessive condensation of OH groups broadens the molecular weight distribution and causes uncontrolled branching of the resin, affecting the density and uniformity of subsequent coatings; too low a temperature results in a slow hydrolysis rate, incomplete reaction, and residual... OCH3 can affect the further crosslinking and adhesion of the resin. The temperature maintained by the water bath can smoothly transition to the condensation stage, avoiding sudden temperature changes that could lead to abrupt changes in the condensation rate. This promotes more uniform growth of the resin molecular chains and more controllable structure, laying the foundation for the subsequent preparation of structurally uniform and stable organosilicon resins for further use in heavy-duty anti-corrosion coatings.

[0052] Stirring facilitates the full dissolution and mixing of materials during the reaction, distributes reaction heat evenly throughout the system, avoids local overheating or undercooling, and ensures the uniformity of the reaction.

[0053] An acidic environment is conducive to catalyzing the hydrolysis reaction, increasing the reaction rate, and inhibiting the self-condensation of silanol groups, thus preventing excessive condensation and resin agglomeration, which would affect the density of the subsequent film formation. In this stage, hydrolysis is dominant, and the resulting silanol oligomers grow more uniformly, which is beneficial for forming small-sized and uniformly distributed organosilicon resins. The resulting film is denser and more transparent, with lower resistance to chemical media (acids, alkalis, salts), and is expected to be widely used in heavy-duty anti-corrosion coatings.

[0054] Furthermore, hydrochloric acid or acetic acid can be used as the pH adjuster.

[0055] In a specific embodiment of the invention, the acid used as the pH adjuster is hydrochloric acid with a concentration of 0.1 mol / L, and its dosage is 0.6%-0.8% of the total mass of the organosilicon resin raw materials; further, it is about 0.7%.

[0056] In an optional embodiment, the addition of γ-aminopropyltriethoxysilane should be performed after the hydrolysis reaction. It should be mixed with anhydrous ethanol at a mass ratio of 1:1 and slowly added dropwise to the reaction system. The addition should be made when the hydrolysis endpoint is reached, the system is free of obvious acid mist, and the solution is clear. The dropwise addition time should be ≥15 min, and the temperature range should be maintained at 50℃-60℃. After the dropwise addition is completed, the mixture should be kept warm and stirred for 30 min, and then the temperature should be raised to 60-80℃ for a polycondensation reaction for 2-3 h. Furthermore, the dripping time is 1-1.5 hours.

[0057] In an optional embodiment, the polycondensation reaction includes: adding γ-aminopropyltriethoxysilane and solvent in a mass ratio of 1:(0.9-1.2) to the system after hydrolysis reaction, at a temperature of 50℃-60℃, a reaction time of ≥45min, and a molar ratio of methylphenyldimethoxysilane to γ-aminopropyltriethoxysilane of 4:(1-3); then carrying out a polycondensation reaction at a temperature of 60℃-80℃ for 2h-3h. And / or, the neutralization reaction temperature is 35℃-50℃, the time is 25min-35min, and the pH of the system after neutralization is 7.0-7.5; the neutralizing agent is selected from at least one of ammonia and triethylamine; And / or, the temperature for the alcohol removal treatment is 63℃-68℃, and the time is 20min-30min; And / or, the temperature for vacuum dehydration is 50℃-60℃, the pressure is -0.06MPa to -0.08MPa, and the time is 40min-60min.

[0058] It should be noted that after the hydrolysis reaction is complete, when there is no obvious acid mist in the system and the solution is clear, γ-aminopropyltriethoxysilane and solvent are added to the system after the hydrolysis reaction, and stirring is required during this process. The addition time needs to be controlled to be >15 minutes to ensure that the newly added substance is fully mixed with the system. Then, the reaction is maintained at a certain temperature for at least 30 minutes. After the temperature maintenance is completed, the system is heated again to carry out the polycondensation reaction. The polycondensation reaction is completed when the system becomes transparent and the viscosity increases. The total time for the hydrolysis reaction and the polycondensation reaction is ≤6 hours.

[0059] Neutralization significantly reduces free hydrogen ions in the system, ensuring the stability of the molecular weight and branching degree of the hydrolyzed oligomers, preventing uncontrollable excessive condensation during storage or subsequent heating, and guaranteeing the storage stability of the resin solution. It also prevents acidic groups from interfering with the chemical stability of the main resin, ensuring the compatibility of the organic-inorganic hybrid system and preventing gelation, delamination, or discoloration of the coating after mixing. Furthermore, it prevents strong acids from causing excessively rapid consumption of the curing agent, leading to explosive polymerization or insufficient reaction, ensuring uniform crosslinking density of the coating, thereby improving its density and chemical resistance. In addition, reducing free hydrogen ions also helps protect the application equipment and the substrate, ensuring long-term adhesion and corrosion protection of the coating.

[0060] The alcohol and water in the system are small-molecule byproducts. If they remain in the resin, they may continue to participate in slow hydrolysis / condensation under the influence of residual hydrogen ions, causing the resin viscosity to gradually increase or even gel during storage. Water in the resin can form a microscopic separated phase, affecting compatibility with the organic resin. Furthermore, as the solvent evaporates and cross-links to cure, the generated water / alcohol molecules migrate and evaporate from the inside of the coating, easily leaving micropores, pinholes, or causing blistering.

[0061] Removing the generated water / alcohol can disrupt the chemical equilibrium, forcing the reaction to proceed to the right, thus allowing Si to... OH further condenses to form polymers with higher molecular weights or denser prepolymers, thereby increasing the solid content of the resin and the crosslinking density after film formation.

[0062] In addition, dehydration continues until no obvious droplets flow out of the condenser, and the system is transparent and uniform, without turbidity or stratification.

[0063] In an optional embodiment, the mass ratio of γ-aminopropyltriethoxysilane to solvent is 1:(0.9-1.2); the mass ratio of γ-aminopropyltriethoxysilane to solvent can be selected from any one of 1:0.9, 1:1, 1:1.1 and 1:1.2, or other values ​​in the range of 1:(0.9-1.2).

[0064] Furthermore, the mass ratio of γ-aminopropyltriethoxysilane to anhydrous ethanol is 1:1.

[0065] In an optional embodiment, after dehydration treatment, the system is further cooled to 25°C-35°C and the kinematic viscosity of the system is adjusted to 180 mPa·s-380 mPa·s to obtain an organosilicon resin.

[0066] After removing water / alcohol, the viscosity of the resin system will change, and it needs to be adjusted to a range suitable for construction. At the same time, it also reduces the emission of volatile organic compounds (VOCs) at the construction site, making it more environmentally friendly.

[0067] It should be noted that the viscosity-adjusting reagent is the same as the reaction solvent to avoid introducing new impurities. It is selected from at least one of n-butanol, isopropanol, and anhydrous ethanol. After adjusting the viscosity of the system, continue stirring for 18-25 minutes until the system is homogeneous and the scraper is free of particles and streaks. Then, precisely filter to obtain the transparent resin, which is the qualified organosilicon resin, specifically an amino-cured environmentally friendly methylphenyl fluorosilane silicone resin.

[0068] The kinematic viscosity of the resin system is tested using conventional methods, such as the capillary viscometer method and the Forecast cup method. The appropriate method should be selected based on actual needs.

[0069] In summary, the method for preparing the organosilicon resin provided in the embodiments of the present invention specifically includes the following steps: (1) The raw materials of organosilicon resin, except for γ-aminopropyltriethoxysilane, are mixed with solvent in proportion, and then hydrolyzed under an inert atmosphere, at a temperature of 50℃-60℃ and under water bath heating. The raw materials include methylphenyldimethoxysilane, dimethyldimethoxysilane, methyltrimethoxysilane, and trifluoropropyltrimethoxysilane in a molar ratio of 4:(2-5):2.5:(1-3). The raw materials are weighed according to the ratio and added to a four-necked flask with auxiliary stirring (300r / min-400r / min) to promote uniform mixing. A solvent (at least one of n-butanol, isopropanol, or anhydrous ethanol) with a mass ratio of 1:(0.9-1.2) to the total mass of the raw materials is added, and N2 is introduced for protection while stirring at normal pressure. A 0.1mol / L hydrochloric acid solution is added dropwise while stirring. After the addition is complete, the mixture is kept warm and stirred continuously for 1-2 hours for hydrolysis.

[0070] Ultimately, the pH of the hydrolysis reaction system was 2.0-4.0.

[0071] (2) After the hydrolysis reaction is complete, when there is no obvious acid mist in the system and the solution is clear, slowly add the uniformly mixed solution of γ-aminopropyltriethoxysilane and anhydrous ethanol at a mass ratio of 1:(0.9-1.2) to the reaction system dropwise. The dropwise addition time should be ≥15 min, and the temperature range should be maintained at 50℃-60℃. After the dropwise addition is completed, keep the temperature and stir for 30 min. Raise the temperature to 60℃-80℃ and continue stirring at low speed for 2-3 h until the system becomes transparent and the viscosity increases, thus completing the polycondensation reaction. The total time of the hydrolysis reaction and the polycondensation reaction should be ≤6 h, and the molar ratio of methylphenyldimethoxysilane to γ-aminopropyltriethoxysilane should be 4:(1-3).

[0072] (3) After neutralization reaction, alcohol removal treatment and vacuum dehydration treatment, organosilicon resin is obtained.

[0073] The neutralization reaction was carried out at a temperature of 35℃-50℃ for 25min-35min, and the pH of the neutralized system was 7.0-7.5. The neutralizing reagent was selected from at least one of ammonia and triethylamine.

[0074] The alcohol removal process is carried out at a temperature of 63℃-68℃ for 20-30 minutes; this stage also includes stirring under normal pressure.

[0075] The dehydration process is carried out at a temperature of 50℃-60℃, a pressure of -0.06MPa to -0.08MPa, and a time of 40min-60min. Dehydration continues until no obvious droplets flow out of the condenser, and the system is transparent and homogeneous, without turbidity or stratification.

[0076] After dehydration, the system is cooled to 25℃-35℃, and n-butanol is added to adjust the kinematic viscosity of the system to 180mpa·s-380mpa·s. Then, the system is continuously stirred for 18min-25min until it is homogeneous and there are no particles or streaks on the scraper. After that, the transparent resin is obtained by precise filtration, which is the required organosilicon resin.

[0077] Thirdly, the present invention provides a heavy-duty anti-corrosion coating, comprising an organosilicon resin as described in any of the foregoing embodiments or an organosilicon resin prepared by any of the foregoing embodiments.

[0078] The heavy-duty anti-corrosion coating provided by this invention has super hydrophobicity and super UV resistance; the small size effect and macroscopic quantum tunneling effect enable it to produce a seepage-proof effect, and it has thermal, light and chemical stability, improving the product's anti-aging, chemical resistance, corrosion resistance and acid and alkali resistance, high salt spray resistance, and effectively protecting metal structures from corrosion; it can also significantly improve the carbonation resistance and chloride ion penetration resistance of concrete.

[0079] Specifically, the protective performance of the coating is achieved through the synergistic effect of the small size of nanoparticles, the macroscopic quantum tunneling effect, and the seepage blocking effect.

[0080] Among them, the nanoparticles are at the nanoscale, with particle size similar to the molecular chain segments of siloxane and the wavelength of ultraviolet light, exhibiting a significant small size effect: forming a strong anchoring structure at the organic-inorganic interface, restricting the slippage of resin polymer chains, dispersing internal stress, and improving the hardness, adhesion and impact resistance of the paint film; it can also fill the micropores and molecular gaps formed by the shrinkage of resin curing, reducing the porosity of the coating from a microscopic level, and relying on physical barriers to block the penetration of corrosive media such as water and chloride ions. At the same time, the nanoparticles can scatter and absorb ultraviolet light, protecting the C-Si bonds and side chain CF bonds of the silicone resin, and improving the aging resistance of the coating.

[0081] Nanoparticles dispersed in an insulating fluorosilicone resin matrix are isolated from each other, and the alternating arrangement of the two phases constructs a nanoscale insulating barrier system, triggering a macroscopic quantum tunneling effect: under the drive of ambient temperature and the electric field of the corrosion micro-battery, electrons can pass through the resin insulating barrier by quantum tunneling and migrate directionally between the non-contacting nanofillers, uniformly dissipating the corrosion charge accumulated at the substrate interface, inhibiting the dissolution of the metal anodic dissolution, and hindering the development of corrosion from an electrochemical perspective, thus endowing the coating with electrostatic dissipation and long-term electrochemical anti-corrosion capabilities.

[0082] The seepage-blocking effect runs through the entire film formation and service life: During the coating curing stage, the capillary suction generated by the liquid resin and the dragging effect of the liquid flow drive the nanoparticles to spontaneously penetrate into the original micropores and microcracks of the paint film. As the silicone resin gradually cross-links and cures, the nanoparticles that have penetrated into the pores accumulate and block in situ, completing the static sealing and plugging during the film formation stage. The synergistic effect of the three mechanisms gives this coating excellent physical shielding, electrochemical corrosion protection and self-blocking capabilities, making it suitable for heavy corrosion protection and weather protection scenarios.

[0083] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0084] Example 1 This embodiment provides a method for preparing organosilicon resin, including the following steps: (1) Mix the raw materials of organosilicon resin with solvent in proportion, and carry out hydrolysis reaction under inert atmosphere, temperature of 55℃ and water bath heating; wherein, the raw materials include methylphenyl dimethoxysilane, dimethyl dimethoxysilane, methyltrimethoxysilane, trifluoropropyltrimethoxysilane and γ-aminopropyltriethoxysilane in molar ratio of 4:3:2.5:2:1; wherein γ-aminopropyltriethoxysilane is weighed separately for later use, and the other 4 are mixed for later use; the mixture of the 4 raw materials is put into a four-necked flask for auxiliary stirring (350r / min) to promote uniform mixing of raw materials; add solvent (n-butanol) with a total mass ratio of 1:1 with the raw materials in the mixture, introduce N2 for protection, and stir at normal pressure; while stirring, add hydrochloric acid with a concentration of 0.1mol / L dropwise, and after the addition is complete, continue to keep warm and stir, and the hydrolysis reaction is carried out for 1.5h.

[0085] Ultimately, the pH of the hydrolysis reaction system was 2.0-4.0.

[0086] (2) After the hydrolysis reaction is complete, when there is no obvious acid mist in the system and the solution is clear, slowly add the uniformly mixed solution of γ-aminopropyltriethoxysilane and anhydrous ethanol in a mass ratio of 1:1 to the reaction system dropwise. The dropwise addition time should be ≥15 min, and the temperature range should be maintained at 55℃. After the dropwise addition is completed, keep the temperature and stir at a constant speed (350 r / min) for 30 min. Raise the temperature to 70℃, reduce the speed to 200 r / min and stir for 3 h until the system becomes transparent and the viscosity increases, thus completing the polycondensation reaction. The total time for the hydrolysis reaction and the polycondensation reaction is 6 h, and the molar ratio of methylphenyldimethoxysilane to γ-aminopropyltriethoxysilane is 4:1.

[0087] (3) After neutralization reaction, alcohol removal treatment and vacuum dehydration treatment, organosilicon resin is obtained.

[0088] The neutralization reaction was carried out at a temperature of 40℃ for 30 minutes, and the pH of the neutralized system was 7.5. The neutralizing agent was ammonia.

[0089] The alcohol removal process was carried out at 65°C for 25 minutes; this stage also included stirring under normal pressure.

[0090] The dehydration process was carried out at a temperature of 55℃, a pressure of -0.06MPa to -0.08MPa, and a time of 50 minutes. Dehydration continued until no obvious droplets flowed out of the condenser, and the system was transparent and homogeneous, without turbidity or stratification.

[0091] Tests showed that the solid content of the silicone resin at this time was 55%-65%, its viscosity was 25s-45s (Ford Cup 4), and its kinematic viscosity was 300mpa·s-500mpa·s.

[0092] After dehydration, the system is cooled to 30°C, and n-butanol is added to adjust the kinematic viscosity of the system to 280 mPa·s-380 mPa·s. Then, the system is continuously stirred for 20 minutes until it is homogeneous and there are no particles or streaks on the scraper. After that, the transparent resin is obtained by precise filtration, which is the required organosilicon resin.

[0093] Comparative Example 1 This comparative example provides a method for preparing an organosilicon resin, the only difference from Example 1 being the order of addition of aminosilanes and process control; the specific steps are as follows: (1) Mix the raw materials of organosilicon resin with solvent in proportion, and carry out hydrolysis reaction under inert atmosphere, temperature of 55℃ and water bath heating; wherein, the raw materials include methylphenyl dimethoxysilane, dimethyl dimethoxysilane, methyltrimethoxysilane, trifluoropropyltrimethoxysilane and γ-aminopropyltriethoxysilane in molar ratio of 4:3:2.5:2:1; put the mixture of all raw materials into a four-necked flask and stir (350r / min) to promote uniform mixing of raw materials; add solvent (n-butanol) with a total mass ratio of 1:1 with the raw materials in the mixture, introduce N2 for protection, and stir at normal pressure; while stirring, add hydrochloric acid with a concentration of 0.1mol / L dropwise, and after the addition is complete, continue to keep warm and stir, and the hydrolysis reaction is carried out for 1.5h.

[0094] Ultimately, the pH of the hydrolysis reaction system was 2.0-4.0.

[0095] (2) After the hydrolysis reaction is completed, when there is no obvious acid mist in the system and the solution is clear, the temperature is raised to 70℃ and the stirring speed is reduced to 200 r / min for 3 hours until the system becomes transparent and the viscosity increases, thus completing the polycondensation reaction. The total time for the hydrolysis reaction and the polycondensation reaction is 6 hours.

[0096] (3) After neutralization reaction, alcohol removal treatment and vacuum dehydration treatment, organosilicon resin is obtained.

[0097] The neutralization reaction was carried out at a temperature of 40℃ for 30 minutes, and the pH of the neutralized system was 7.5. The neutralizing agent was ammonia.

[0098] The alcohol removal process was carried out at 65°C for 25 minutes; this stage also included stirring under normal pressure.

[0099] The dehydration process was carried out at a temperature of 55℃, a pressure of -0.06MPa to -0.08MPa, and a time of 50 minutes. Dehydration continued until no obvious droplets flowed out of the condenser, and the system was transparent and homogeneous, without turbidity or stratification.

[0100] Tests showed that the solid content of the silicone resin at this time was 55%-65%, its viscosity was 25s-45s (Ford Cup 4), and its kinematic viscosity was 300mpa·s-500mpa·s.

[0101] After dehydration, the system is cooled to 30°C, and n-butanol is added to adjust the viscosity of the system to 180 mPa·s-380 mPa·s. Then, the system is continuously stirred for 20 minutes until it is uniform and there are no particles or streaks on the scraper. After that, the transparent resin is obtained by precise filtration, which is the required organosilicon resin.

[0102] Experimental Example 1 This experiment was conducted to investigate the effect of the amount of trifluoropropyltrimethoxysilane on the properties of organosilicon resin. The preparation steps were the same as in Example 1, except that the molar ratio of trifluoropropyltrimethoxysilane was different. The results are shown in Table 1.

[0103] It should be noted that this experimental example studies the effect of the amount of fluorine functional groups introduced on the properties of organosilicon resin. As a comparison, it is necessary to exclude the influence of other functional groups on the functionality of the main resin. Therefore, this experiment was conducted without the addition of γ-aminopropyltriethoxysilane.

[0104] Table 1 Effect of Trifluoropropyltrimethoxysilane Dosage on the Properties of Organosilicon Resins

[0105] As can be seen from the results in Table 1, the resin exhibits the best overall performance when the molar ratio of trifluoropropyltrimethoxysilane is 2, which is also beneficial for the preparation of heavy-duty anti-corrosion coatings in the later stages.

[0106] Experimental Example 2 This experiment was conducted to investigate the effect of the amount of γ-aminopropyltriethoxysilane on the properties of organosilicon resin. The preparation steps were the same as in Example 1, except that the molar ratio of γ-aminopropyltriethoxysilane was different. The results are shown in Table 2.

[0107] Table 2 Effect of γ-aminopropyltriethoxysilane dosage on the properties of organosilicon resins

[0108] As can be seen from the results in Table 2, if only self-crosslinking curing and on-site preparation are considered, the resin performance is best when the molar ratio of γ-aminopropyltriethoxysilane is 2. However, considering the suitability for subsequent coating preparation, on-site construction, and long-term storage of coatings, and the fact that the curing agent can be added and mixed on-site, the optimal ratio is when the molar ratio of γ-aminopropyltriethoxysilane is 1. Therefore, the present invention sets the molar ratio of γ-aminopropyltriethoxysilane to 1.

[0109] Experimental Example 3 This experimental example is used to analyze and compare the preparation processes of the silicone resin in Example 1 and Comparative List 1. Specifically: Example 1 uses a stepwise method for resin synthesis. The advantage of this method is that the amino-free silane monomer is first hydrolyzed under acidic conditions to form hydroxyl-terminated oligomeric siloxanes. Then, γ-aminopropyltriethoxysilane is slowly added dropwise to allow it to undergo a grafting condensation reaction with the hydroxyl groups of the oligomeric siloxanes. This avoids the self-polymerization reaction of γ-aminopropyltriethoxysilane and achieves a uniform distribution of amino groups. The synthesized resin has the characteristics of uniform molecular weight, strong storage stability, transparency, uniform and controllable curing, and excellent adhesion strength and water resistance.

[0110] Compared to the one-step method used in Comparison List 1, which involves adding all raw materials together for controlled synthesis, the main challenge in controlling this method and its impact on the performance of silicone resin lies in the fact that γ-aminopropyltriethoxysilane will intervene in the reaction during acid catalysis, adversely affecting the silicone resin. If not properly controlled, it can lead to uneven molecular weight distribution of the resin, potentially resulting in excessively high amino content in some areas; or even phase separation. γ-aminopropyltriethoxysilane may undergo self-polymerization under acidic catalysis, leading to uneven curing and subsequent brittleness due to uneven crosslinking density.

[0111] Application Example 1 This application example provides a heavy-duty anti-corrosion coating, the preparation of which includes the following steps: Accurately weigh 50 parts of the silicone resin synthesized in Example 1, 0.8 parts of BYK111, 0.5 parts of BYK333, 0.3 parts of BYK1790, 0.5 parts of AKN-3386, 20 parts of 1250 mesh R-706, 8 parts of 2000 mesh ultrafine barium sulfate, 5 parts of ultrafine mica powder, 8 parts of ultrafine calcium carbonate, 1 part of nano-graphene, 1.5 parts of organobentonite, 0.4 parts of BYK100, and 4 parts of n-butanol. After high-speed stirring and low-speed defoaming processes according to conventional production technology, grind the mixture until the fineness is ≤30μm to obtain a heavy-duty anti-corrosion coating.

[0112] It should be noted that the preparation process of the heavy-duty anti-corrosion coating in this application example is a routine operation in the field and is not particularly limited. It can be reasonably selected according to actual needs.

[0113] Application Example 2 This application example provides a heavy-duty anti-corrosion coating, the preparation steps of which are the same as those in Application Example 1, the only difference being: The synthesized silicone resin is the same silicone resin prepared in Comparative Example 1, and its dosage is 50 parts.

[0114] Test Example 1 The heavy-duty anti-corrosion coatings prepared according to test cases 1-2 were subjected to relevant performance tests, and the relevant results are shown in Table 3.

[0115] Table 3 Performance test results of heavy-duty anti-corrosion coatings

[0116] As can be seen from the data in Table 3, the heavy-duty anti-corrosion coating prepared using the silicone resin obtained in Example 1 as raw material has excellent performance in all resistance index tests. In particular, the weather resistance index can reach >2000h and the salt spray resistance can reach >2500h, which surpasses most conventional resins on the market and has great promotion value.

[0117] In summary, the organosilicon resin provided by this invention is a green and environmentally friendly resin, in which harmful substances such as formaldehyde, benzene, toluene, xylene, and heavy metals do not exceed the detection limits required by relevant standards; it can be cured into a film at room temperature without the need for heating or other means to promote curing; the introduction of fluorine functional groups with lower surface energy significantly improves its various technical indicators; it has wide applicability and can meet the protection requirements of concrete and steel structures under various environmental conditions; it has strong environmental adaptability and can adapt to dry and wet, freeze-thaw, marine, and highly corrosive environments; and it requires only one application with low subsequent maintenance costs.

[0118] The preparation process of silicone resin is simple and the steps are simplified. It can be applied by conventional spraying, rolling, or brushing without the need for special equipment.

[0119] Heavy-duty anti-corrosion coatings made from organosilicon resins have superior hydrophobicity, strong UV resistance, thermal, light, and chemical stability. They are beneficial for improving the product's anti-aging, chemical resistance, corrosion resistance, acid and alkali resistance, and salt spray resistance, effectively protecting metal structures from corrosion. They can also significantly improve the carbonation resistance and chloride ion penetration resistance of concrete.

[0120] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. An organosilicon resin, characterized in that, Including difunctional and trifunctional silanes with a molar ratio of (6-9):(2.5-8.5); The difunctional silane is selected from at least one of methylphenyldimethoxysilane, dimethyldimethoxysilane, and methylphenylfluoroalkylsilane; The trifunctional silane is selected from at least one of methyltrimethoxysilane, trifluoropropyltrimethoxysilane, and γ-aminopropyltriethoxysilane.

2. The organosilicon resin according to claim 1, characterized in that, The difunctional silanes include methylphenyldimethoxysilane and dimethyldimethoxysilane in a molar ratio of 4:(2-5).

3. The organosilicon resin according to claim 1, characterized in that, The trifunctional silanes include methyltrimethoxysilane, trifluoropropyltrimethoxysilane and γ-aminopropyltriethoxysilane in a molar ratio of 2.5:(1-3):(1-3).

4. A method for preparing the organosilicon resin according to any one of claims 1-3, characterized in that, Includes the following steps: The raw materials of organosilicon resin are mixed with solvent in proportion, and then hydrolyzed under an inert atmosphere at a temperature of 50℃-60℃. After the hydrolysis reaction is completed, the temperature is raised to 60℃-80℃ to carry out a polycondensation reaction. After neutralization reaction, alcohol removal treatment and vacuum dehydration treatment, organosilicon resin is obtained. The total time for hydrolysis and condensation reactions is ≤6h.

5. The preparation method according to claim 4, characterized in that, The ratio of the total mass of the raw materials of the silicone resin to the mass of the solvent is 1:(0.9-1.2). The raw materials of the organosilicon resin include methylphenyl dimethoxysilane, dimethyl dimethoxysilane, methyltrimethoxysilane and trifluoropropyltrimethoxysilane in a molar ratio of 4:(2-5):2.5:(1-3); the solvent is selected from at least one of n-butanol, isopropanol and anhydrous ethanol.

6. The preparation method according to claim 5, characterized in that, The solvent comprises n-butanol and anhydrous ethanol in a mass ratio of 1:(0.8-1.1).

7. The preparation method according to claim 4, characterized in that, The hydrolysis reaction has at least one of the following characteristics: Feature 1: The hydrolysis reaction takes place in a water bath environment for 1-2 hours; Feature 2: The hydrolysis reaction is subjected to stirring at a speed of 300 r / min-400 r / min; Feature 3: The pH of the hydrolysis reaction system is 2.0-4.0, and the pH adjuster is selected from at least one of hydrochloric acid, sulfuric acid, citric acid, phosphoric acid and acetic acid; the amount of pH adjuster used is 0.6%-0.8% of the total amount of organosilicon resin raw materials.

8. The preparation method according to claim 4, characterized in that, The polycondensation reaction includes: adding γ-aminopropyltriethoxysilane and solvent in a mass ratio of 1:(0.9-1.2) to the system after hydrolysis reaction, at a temperature of 50℃-60℃, a reaction time of ≥45min, and a molar ratio of methylphenyldimethoxysilane to γ-aminopropyltriethoxysilane of 4:(1-3); then carrying out a polycondensation reaction at a temperature of 60℃-80℃ for 2h-3h. And / or, the neutralization reaction is carried out at a temperature of 35℃-50℃ for 25min-35min, and the pH of the neutralized system is 7.0-7.5; the neutralizing agent is selected from at least one of ammonia and triethylamine; And / or, the temperature of the alcohol removal treatment is 63℃-68℃, and the time is 20min-30min; And / or, the dehydration temperature is 50℃-60℃, the pressure is -0.06MPa to -0.08MPa, and the time is 40min-60min.

9. The preparation method according to claim 4, characterized in that, The dehydration process further includes cooling the system to 25℃-35℃ and adjusting the kinematic viscosity of the system to 180mpa·s-380mpa·s to obtain an organosilicon resin.

10. A heavy-duty anti-corrosion coating, characterized in that, Includes the silicone resin as described in any one of claims 1-3 or the silicone resin prepared by the preparation method as described in any one of claims 4-9.